Psychosocial predictors and moderators of weight management programme outcomes in ethnically diverse obese youth. Issue 6 (7th July 2016) - Taylor, J. H.; Xu, Y.; Li, F.; Shaw, M.; Dziura, J.; Caprio, S.; Tamborlane, W. V.; Nowicka, P.; Savoye, M.
Summary: Background: An important area of research in childhood obesity is the identification of factors that predict or moderate the responses to obesity intervention programmes, yet few studies have examined the impact of self‐esteem and family functioning on obesity treatment outcomes. Objectives: We sought to determine whether baseline self‐esteem and family functioning predicted or moderated childhood obesity intervention outcomes at 6 months. Methods: From 2009 to 2011, seventy‐five 10–16 year old, racially/ethnically diverse obese youths with abnormal glucose tolerance were randomized to 6 months of an intensive family‐based obesity lifestyle intervention (Bright Bodies) or routine outpatient Clinic Care. We examined youth self‐concept, parent‐rated family functioning and 6‐month outcomes (youths' glucose tolerance, weight, body mass index and percent fat). We set the significance threshold as P ≤ 0.05 for moderator and predictor analyzes. Results: Having poor family functioning and self‐concept scores indicating high anxiety and low self‐esteem at baseline predicted poor 6‐month outcomes overall (Bright Bodies and Clinic Care groups combined). Additionally, baseline self‐esteem and family functioning moderated treatment effects such that Bright Bodies outperformed Clinic Care in youths with low self‐esteem and poorly functioning families, whereas youths with high self‐esteem and high‐functioning families did similarly well with either intervention. Discussion: Our findings suggest intensive family‐based lifestyle programmes are particularly beneficial for youth with low self‐esteem and poorly functioning families.